Enhancing Student's Understanding of the Rupiah's Characteristics and Security Elements Through Hands-On Investigation: Classroom Action Research - Amalina, Endah Nur; Astriani, Erni; Jawanoko, Nashru Aji; Afdhila, Qory; Prastika, Titis Dwi; Dewi, Retno Mustika; Hadiyanto, Herman (Jurnal Pendidikan Ekonomi, 2025)
This study aims to improve the learning outcomes of grade X students in phase E, senior high school in Indonesia, on the material of characteristics and security elements of the Rupiah currency by applying the hands-on investigation model. The background of the study was the low learning outcomes of students on the material of payment instruments, especially the characteristics and security elements of Rupiah, because the characteristics of the material are conceptual and abstract, and the use of lecture methods is less effective. The research method used is Collaborative Classroom Action Research between researchers, economics teachers, and lecturers, which is carried out in two stages, namely pre-cycle and cycle. Each cycle consists of planning, implementation, observation, and reflection stages. In cycle I, learning is carried out using the 3D method (seen, touched, and held up to the light) to identify the authenticity of Rupiah. In cycle II, using UV lights as additional media to detect invisible security elements enhances learning. The results of the study showed an increase in the average value of students from 55.64 (pre-cycle) to 71.39 (cycle I) and increased significantly to 88.91 (cycle II). The percentage of learning objective achievement also increased from 27% (pre-cycle), 61% (cycle I), to 90.9% (cycle II). The study results prove that the hands-on investigation model effectively improves students' understanding of the material and the authenticity of the Rupiah.